Existing shariah model of Islamic home loan financing: Weakness and strengthen - Sharifah Arni, Syed Jaaffar; Puspa Liza, Ghazali; Bunyamin, Bello; Saiful Bahri, Mohamed (2017)
Islamic banks in Malaysia offer a wide range of products, for instance from basic Shariah compliant retail products to insurance, mortgages, investment instruments and large-scale project financing. This article emphasizes on the strength and weaknesses of 3 most top Shariah principles practiced for home financing in Malaysia.The top listed Shariah principles in Malaysia are Bai Bithaman Ajil (deferred payment sale), Musyarakah Mutanaqisah (diminishing partnership) and Tawarruq (direct instrument of debt creation. According to the strength and weaknesses of the existing Islamic home financing, the new model of Islamic home financing must be developed especially for lower incomes earners.